Evaluation of ribavirin efficacy and tolerance in subjects with chronic hepatitis C virus infection - Stanimirović Violeta; Nikolić Dejan; Stanimirović Branko; Nikolić Aleksandra; Čučak Spomenka (Vojnosanitetski Pregled)
Background. Reports by hepatologists indicated that anti-HCV antibodies might be detected in 71% to 84% of cases of post-transfusion hepatitis and in up to 50% of cases of sporadic non-A non-B hepatitis. Anti-HCV antibodies were detected in 0.05-1% of blood donors with normal alanine transaminase (ALT) levels and negative anti-HBc screening. Anti-HCV antibodies were found in 67% of patients with a history of intravenous drug abuse or autoimmune hepatitis, and in 10-30% of patients with hepatocellular carcinoma. This indicated that hepatitis C virus was a major cause of the acute and chronic hepatitis throughout the world. Methods. This was a multicentric, international, double-blind, randomized, placebo-controlled study. After the eight-week screening period, patients were randomized to receive daily ribavirin 1200 mg or placebo, during the 48-week treatment period. Follow-up observations were performed during a 16 week post-treatment period. Up to 80 male and female outpatients with mild to moderate chronic active hepatitis C virus infection were enrolled in this study. Results. During the treatment period ALT values were significantly lower in the ribavirin group. Neither in the ribavirin group, nor in the placebo group significant statistical differences of the HCV RNA values were found. Significantly lower portal inflammation was noticed in ribavirin group after the treatment. Analysis of laboratory data demonstrated that ribavirin therapy was associated with mild to moderate reversible anemia. Investigator’s evaluation of the effect of the therapy on patient’s well being showed statistically significant differences in the benefit of the ribavirin group. Conclusion. In this study ribavirin was more effective than placebo in reducing ALT levels during the treatment period of the applied therapy in patients with chronic active hepatitis C.